Metals in the Environment: Philosophy and Action by the Metals Industry - Conard, Bruce (Geoscience Canada, 2001)
Summary A critical issue facing our industrial society is to determine how to continue the beneficial use of metals while minimizing adverse effects metal releases may have on people or the environment. The best way to examine potential adverse effects is to carry out risk assessments. The metals resource industry and certain federal government departments have taken aproactive approach to gaining needed information for risk assessments on metals by forming the Metals in the Environment (MITE) Research Network. This Network, receiving significant funding from NSERC for university research across Canada, is administering a 5-year integrated program defined by government and industry in a truly co-operative and integrated fashion. The program is focussing on: sources of metals, both industrial and natural; processes that move and control metal species; and impacts of metals on flora and fauna.